Assessing the Effectiveness of Water Filtration Machine in Providing Safe Drinking Water in Pagoh Area - Zamzam, Muhammad Faiq; Rosli, Mohd Arif (Progress in Engineering Application and Technology, 2024)
The purpose of this study was to investigate the physicochemical quality of treated water from paid water filter machines, as well as to assess the health level of drinking treated water paid for by users in the Pagoh region using a questionnaire. This research collected 11 water samples from paid filtration units in and around Pagoh, Johor. A dissolved metre is used to determine pH, turbidity, Total Suspended Solid, conductivity, and dissolved oxygen in air, while an ICP-MS technique is used to determine mineral content such as magnesium. A sample of treated water from a paid water filter machine is taken once and tested 3 times to obtain an average value. The pH value, turbidity, total dissolved solids of the study sample water, conductivity and heavy metal (Mg) concentration values obtained are at safe levels for drinking. The determination of the pH value shows that the pH range of the entire sample is between 6.98 to 12 where this range of 7 shows that the pH of the sample is within the recommended standard range and for the turbidity range of all samples is 0.24 to 0.52 NTU. Total Suspended Solids also showed that all samples were within the set standard range of 2.67 to 4.00 mg/L and the range for conductivity was also within a safe range of 137.53 to 166.53 μS/cm. Additionally, the range for dissolved oxygen was 6.09 to 9.03 mg/L. Meanwhile, for heavy metal parameters (Mg) are also in a safe range of 1.78 to 2.11 mg/L. The physiochemical parameters of the water sample were determined using the Malaysian Drinking Water Quality Standard (MDWQS). The questionnaire showed that the majority of survey data that assessed individual experiences and perceptions related to air quality and the use of water purifiers presented a picture of health-related outcomes. Respondents reported relatively low adverse health events such as symptoms (Mean = 2.05, SD = 1.226), sore throat (Mean = 2.51, SD = 1.026), and poisoning or vomiting (Mean = 2.21, SD = 0.928) associated with water from the filter machine. These findings suggest a general contradiction with the notion that using a water filtration affects negative health outcomes.